PENGGUNAAN BAHASA MANDARIN SEBAGAI MEDIUM DAKWAH DALAM NGO DI MALAYSIA - Aemy Elyani Mat Zain; Nur Aisyah Abu Hassan; Safinah Ismail; Siti Zahidah Mu’al (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2020)
The use of Mandarin language in Dakwah is remotely practiced by Malaysians. This is because majority of Malaysians especially Muslims are more comfortable using their native language which is Malay language and English as communication language used with mad’u from various backgrounds of religion and language. In fact, there are some more likey to practice dakwah and islah amongs only Muslims. Thus, this study is about a few dakwah movements in Malaysia that using Mandarin as communication language in dakwah movements. The research methodology used is qualitative from documented or written sourceS. The findings show that Mandarin language is an appropriate and relevant medium in dakwah communication because the number of Chinese people in Malaysia is also more than the Indians. The implication of the study found that there are two aspects the using of Mandarin language in Dakwah which are as  preparation to preacher or daie to  deal with Chinese mad’u; Mandarin as a dakwah communication language in facing Chinese mad’u through their organized activities and programs.